Find the Difference!

Algebra Level 2

x x is a positive real number which satisfies

11 x 2 21 x + 31 + 11 x 2 21 x 9 = 8. \sqrt {11x^2-21x+31}+\sqrt {11x^2-21x-9}=8.

What is the value of

11 x 2 21 x + 31 11 x 2 21 x 9 ? \sqrt {11x^2-21x+31}-\sqrt {11x^2-21x-9} ?


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Morgan Blake
Dec 31, 2013

Let a = 11 x 2 21 x + 31 a=\sqrt{11x^{2}-21x+31} and b = 11 x 2 21 x 9 b=\sqrt{11x^{2}-21x-9}

Let I = 11 x 2 21 x + 31 + 11 x 2 21 x 9 I=\sqrt{11x^{2}-21x+31}+\sqrt{11x^{2}-21x-9} and J = 11 x 2 21 x + 31 11 x 2 21 x 9 J=\sqrt{11x^{2}-21x+31}-\sqrt{11x^{2}-21x-9}

Therefore, I = a + b I=a+b and J = a b J=a-b

By the difference of two squares, we have: I J = ( a + b ) ( a b ) = a 2 b 2 IJ=(a+b)(a-b)=a^{2}-b^{2} I J = ( 1 1 2 21 x + 31 ) ( 11 x 2 21 x 9 ) IJ=(11^{2}-21x+31)-(11x^{2}-21x-9) I J = 40 IJ=40

I = 8 I=8 J = 40 8 = 5 J=\frac{40}{8}=\boxed{5}

Mohamed Abdelaaty
Dec 31, 2013

Let's define a 2 = 11 x 2 21 x + 31. a^2 = 11x^2 - 21x + 31.

a 2 + a 2 40 = 8 \sqrt{a^2} + \sqrt{a^2 - 40} = 8

8 a = a 2 40 8-a = \sqrt{a^2 - 40}

a 2 16 a + 64 = a 2 40 = > a = 6.5 a^2 - 16a + 64 = a^2 - 40 => a = \boxed{6.5}

The required is: a a 40 = 6.5 1.75 = 5 a - \sqrt{a-40} = 6.5 - \sqrt{1.75} = \boxed{5}

Rusli Azis
Mar 6, 2014

Let's suppose that a=V(11x^2 -21x +31) and b=V(11x62-21x-9) So we have : Va+Vb=8, then 1/8 = 1/(Va+Vb), by rationalizing, we get 8(Va-Vb)= (a-b), therefore 8(Va-Vb)=40 So, Va-Vb=40/8=5

Budi Utomo
Dec 31, 2013

We must know if (11x^2 - 21x + 31)^1/2 = 13/2, so (11x^2 - 21x - 9)^1/2 = (11x^2 - 21x + 31 - 40 )^1/2 = 3/2. So, (11x^2 - 21x + 31)^1/2 - (11x^2 - 21x - 9)^1/2 = 13/2 - 3/2 = 10/2 = 5.

Let 11 x 2 21 x 9 = p 11x^2-21x-9=p then 11 x 2 21 x + 31 = p + 40 11x^2-21x+31=p+40 . Now we can modify the first equation to the form p + 40 + p = 8 \sqrt {p+40}+\sqrt {p}=8 . And by the same way, the desired form can change to be p + 40 p \sqrt {p+40}-\sqrt {p} .

Note that ( p + 40 + p ) ( p + 40 p ) = ( p + 40 ) p = 40 (\sqrt {p+40}+\sqrt {p})(\sqrt {p+40}-\sqrt {p})=(p+40)-p=40 . By this, we have a new equation now

( p + 40 + p ) ( p + 40 p ) = 40 (\sqrt {p+40}+\sqrt {p})(\sqrt {p+40}-\sqrt {p})=40

8 ( p + 40 p ) = 40 8(\sqrt {p+40}-\sqrt {p})=40

p + 40 p = 5 \sqrt {p+40}-\sqrt {p}=\boxed {5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...